Injury prevention and management in competitive swimming: Intervention and evaluation - Hardt, J.; Gordon, S.; Benjanuvatra, N. (Journal of Science and Medicine in Sport, 2011)
Introduction: The purpose of this study was to implement and evaluate an injury prevention and management program with a competitive swimming squad. In addition to traditional training and rehabilitation behaviours, this intervention focussed on areas of increasing communication and social support among injured athletes. Method: A coach-implemented injury prevention and management program was developed based on the findings from 2 previous studies. Participants included coaches (N=3) and swimmers (N=35) from 3 leading swim clubs in a Western Australian metropolitan area. The intervention lasted the duration of a short-course competitive season (5 months), with one club receiving the coach training intervention. Prior to the outset of the season, the coach of this club underwent consultation and training with the primary investigator to create an injury prevention and management program for their squad. Specific strategies were outlined for each of the 4 phases of injury management: injury prevention, short-term injury management, long-term injury management, and return to full training. To measure the effectiveness of the injury prevention and management program, all swimmers and their coaches completed the Injury Prevention and Management Profile (IPMP) prior to and at the completion of the intervention. The IPMP measured the extent to which the coach performed (or was perceived to perform) a particular management behaviour and how important that behaviour was for injury management. Injury rates and training volume were also measured. Results and Conclusions: IPMP data indicated that for most behaviours, swimmer perceptions of their coach did not alter significantly, regardless of the intervention. Given that no athletes sustained a major injury during the intervention, it was understandable that their perceptions of injury management behaviours would not change significantly. Qualitative data revealed that the swim coach from the intervention squad felt more prepared to manage injury and more at ease with preparing training plans for injured swimmers following the intervention. Despite higher training volumes, the elite swimmers (N=9) reported no injuries over the course of the intervention. However, 11 out of the 26 sub-elite swimmers sustained minor or moderate injuries. It was speculated that elite swimmers had higher body awareness as a result of greater training, and they were more likely to address pain when it was small before it developed into an injury. Future research will aim to implement longer interventions and more sensitive injury measurements to more accurately capture injury data in competitive swimming.